Non-cardia early gastric cancer in Central Vietnam: noticeable uncommon background mucosa and results of endoscopic submucosal dissection - Tran, Van Huy; Tran, Quang Trung; Nguyen, Thi Huyen Thuong; Dang, Cong Thuan; Lerch, Markus M.; Aghdassi, Ali A.; Miayahara, Ryoji (Endoscopy International Open, 2022)
Background and study aims Gastric cancer (GC) is one of the leading causes of malignancy-related death in Vietnam, with increasing incidence of non-cardia early gastric cancer (N-EGC). Data on accurate diagnosis of EGC and treatment by endoscopic submucosal dissection (ESD) in Vietnam are very sparse. The aim of this study was to describe the characteristics of N-EGC and evaluate the effectiveness and the safety of ESD in Central Vietnam.Patients and methods We prospectively enrolled patients with N-EGC detected by magnified chromoendoscopy from December 2013 to August, 2018 in Central Vietnam. Selected cases of N-EGC received standardized ESD technique and have been following up carefully as in protocol. Results Among 606 GC patients, 46 had N-GEC and underwent ESD. The depth of invasion was pT1a in 33 (71.7 %), pT1b1 in 10 (21.7 %), and pT1b2 in three cases (6.6 %). Mild chronic atrophic gastritis, most being C2 (63 %), and gastritis-like EGC that did not appear malignant was the predominant type. ESD achieved a 97.8 % en bloc resection rate; the mean procedure time was 76 ± 22 minutes (range 24–155), and mean endoscopic tumor size was 23 ± 5 mm (range 13–52) and ESD sample size was 28 ± 7 mm (range 16.5–60). Complications consisted of two patients with bleeding and one with a minor perforation, all of which were successfully managed by endoscopy. The longest and the mean follow-up times were 84 and 64 months, respectively, with no recurrence. Conclusions A significant proportion patients with N-EGC have a background mucosa of mild chronic atrophic gastritis. Our results 7 years after starting ESD demonstrate early promising outcomes with the procedure.